Drivers of stunting reduction in Peru: a country case study. (29th August 2020) - Huicho, Luis; Vidal-Cárdenas, Elisa; Akseer, Nadia; Brar, Samanpreet; Conway, Kaitlin; Islam, Muhammad; Juarez, Elisa; Rappaport, Aviva I; Tasic, Hana; Vaivada, Tyler; Wigle, Jannah; Bhutta, Zulfiqar A
ABSTRACT: Background: Peru reduced its under-5 child stunting prevalence notably from 31.3% in 2000 to 13.1% in 2016. Objectives: We aimed to study factors and key enablers of child stunting reduction in Peru from 2000–2016. Methods: Demographic and Health Surveys were used to conduct descriptive analyses [height-for-age z scores (HAZ) means and distributions, equity analysis, predicted child growth curves through polynomial regressions] and advanced regression analyses. An ecological (at department level) multilevel regression analysis was conducted to identify the major predictors of stunting decline from 2000 to 2016, and Oaxaca–Blinder decomposition was conducted to identify the relative contribution of each factor to child HAZ change. A systematic literature review, policy and program analysis, and interviews with relevant stakeholders were conducted to understand key drivers of stunting decline in Peru. Results: The distribution of HAZ scores showed a slight rightward shift from 2000 to 2007/2008, and a greater shift from 2007/2008 to 2016. Stunting reduction was higher in the lowest wealth quintile, in rural areas, and among children with the least educated mothers. Decomposing predicted changes showed that the most important factors were increased maternal BMI and maternal height, improved maternal and newborn health care, increased parental education, migration to urban areas, and reduced fertility. Key drivers included the advocacy role of civil society and political leadership around poverty and stunting reduction since the early 2000s. Key enablers included the economic growth and the consolidation of democracy since the early 2000s, and the acknowledgement that stunting reduction needs much more than food supplementation. Conclusions: Peru reduced child stunting owing to improved socioeconomic determinants, sustained implementation of out-of-health-sector and within-health-sector changes, and implementation of health interventions. These efforts were driven through a multisectoral approach, strong civil society advocacy, and keen political leadership. Peru's experience offers useful lessons on how to tackle the problem of stunting under differing scenarios, with the participation of multiple sectors.